Análise de abrigos termo-higrométricos alternativos para transectos móveis - Valin Jr, Marcos de Oliveira (2019)
The mobile transect method is to perform in a predetermined path recording the measurements of climate data and is a viable option, especially in the investigation of heat islands. Aiming to provide subsidies, techniques and methodologies to urban climate studies using mobile transects, it is proposed as a general objective to analyze the thermo-hygrometric performance of micrometeorological shelters of different typologies for data collection. For the development of the research were identified in the literature the types of shelters for thermohygrometers already studied and quantified for analysis; 5 types of shelters were chosen for the analysis and constructed together with datalogger, the sensors were calibrated to be transected and after validated the data were analyzed statistically. The results of the literature search pointed to the non-standardization of methodological procedures in urban climate studies with the use of transects. The statistical analysis of the experimental part indicated as significant the interactions: Temperature and Shift; Temperature and Period; Humidity and Shift; Humidity and Month; Humidity and Station; Humidity and Period. Non-significant interactions were: Temperature and Month; Temperature and Station; Temperature and Point; Humidity and Point. The commercial shelter adopted was adopted as reference, since it is possible to be used in works anywhere in the world. For studies of heat islands performed at night, all the alternative shelters analyzed were efficient. The alternative model here called "horizontal PVC" presented totally favorable results in all the scenarios and analyzes carried out. The model printed on a 3D printer was effective in almost every situation. The model with "plastic plates" and the "vertical PVC" model were not efficient.